Bimanual grasping does not adhere to Weber’s law - Tzvi Ganel (Nature Portfolio, 2017)
Abstract According to Weber’s law, a fundamental principle of perception, visual resolution decreases in a linear fashion with an increase in object size. Previous studies have shown, however, that unlike for perception, grasping does not adhere to Weber’s law. Yet, this research was limited by the fact that perception and grasping were examined for a restricted range of stimulus sizes bounded by the maximum fingers span. The purpose of the current study was to test the generality of the dissociation between perception and action across a different type of visuomotor task, that of bimanual grasping. Bimanual grasping also allows to effectively measure visual resolution during perception and action across a wide range of stimulus sizes compared to unimanual grasps. Participants grasped or estimated the sizes of large objects using both their hands. The results showed that bimanual grasps violated Weber’s law throughout the entire movement trajectory. In contrast, Just Noticeable Differences (JNDs) for perceptual estimations of the objects increased linearly with size, in agreement with Weber’s law. The findings suggest that visuomotor control, across different types of actions and for a large range of size, is based on absolute rather than on relative representation of object size.